2016
DOI: 10.1111/fwb.12805
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to elevatedpCO2alters post‐treatment diel movement patterns of largemouth bass over short time scales

Abstract: Summary Studies with marine fishes indicate that exposure to elevated partial pressures of CO2 (pCO2) related to climate change have negative consequences for fish behaviour. Freshwater fishes may experience similar increases in pCO2 due to a number of different mechanisms, but there is a paucity of information on how freshwater fishes may respond to exposure to elevated pCO2. To define the effects of elevated pCO2 on a free‐swimming freshwater fish, 19 adult largemouth bass (Micropterus salmoides) were tagg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Increased activity and potentially being bolder can result in fishes having greater risk of being consumed by predators and may shift their habitat‐use (Coleman & Wilson, ). While the current study is one of the first to examine CO 2 ‐induced behavioural changes for an obligate freshwater fish species (Hasler et al ., in press), previous work on marine, temperate and anadromous species have also suggested that exposure to fishes to elevated p CO 2 , even for short durations, can alter behaviour. For example, Munday et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Increased activity and potentially being bolder can result in fishes having greater risk of being consumed by predators and may shift their habitat‐use (Coleman & Wilson, ). While the current study is one of the first to examine CO 2 ‐induced behavioural changes for an obligate freshwater fish species (Hasler et al ., in press), previous work on marine, temperate and anadromous species have also suggested that exposure to fishes to elevated p CO 2 , even for short durations, can alter behaviour. For example, Munday et al .…”
Section: Discussionmentioning
confidence: 97%
“…Previous work has shown that behavioural changes induced by exposure to elevated p CO 2 can be reversed following removal of the CO 2 stimulus, but this potential for recovery has not been well studied. For example, predator avoidance behaviours were re‐established in larval P. wardi after returning to ambient sea water for 2 days (Munday et al ., ), and anxiety behaviours in juvenile splitnose rockfish Sebastes diploproa (Gilbert 1890) affected by CO 2 exposure returned to normal after 12 days in ambient conditions (Hamilton et al ., ), and movement patterns between CO 2 ‐exposed and non‐exposed adult largemouth bass Micropterus salmoides (Lacépède 1802) were no longer different after 11 days (Hasler et al ., in press) probably because previously disrupted cellular ion gradients re‐established. In L. macrochirus , it is possible that additional recovery time at ambient conditions ( i.e .…”
Section: Discussionmentioning
confidence: 99%
“…pH for the acidified treatment was maintained by an Aqua Medic ® CO 2 computer coupled with a solenoid valve and multi‐pH probe (Hasler, Midway, et al, ; Kates, Dennis, Noatch, & Suski, ; Midway et al, ). This was set to a threshold of 6.52, above which the solenoid valve would open and CO 2 gas would bubble through the treatment tank until a pH of 6.50 was achieved.…”
Section: Methodsmentioning
confidence: 99%
“…This was contrasted to the control treatment pH of 8.2 that laboratory stock populations had become adapted to over several generations since their initial collection in -2009(Nilsson, Lundbäck, Postavnicheva-Harri, & Persson, 2011. pH for the acidified treatment was maintained by an Aqua Medic ® CO 2 computer coupled with a solenoid valve and multi-pH probe (Hasler, Midway, et al, 2016;Kates, Dennis, Noatch, & Suski, 2012;Midway et al, 2017). This was set to a threshold of 6.52, above which the solenoid valve would open and CO 2 gas would bubble through the treatment tank until a pH of 6.50 was achieved.…”
Section: Methodsmentioning
confidence: 99%
“…Surface water samples were filtered with 0.45 µm filters (Advantec, Co.) in situ and taken into 5, 15, 15, and 50 ml Nalgene centrifugation tubes for stable isotope, major anion, cation, and nutrient analysis. Porewater samples were taken from the lakeshore aquifers with a push point sampler (M.H.E, Co.) connected to a peristaltic pump (Solinst, Co.) (Luo et al, 2014(Luo et al, , 2016; 100 ml raw surface water or porewater was titrated with a 0.1 µM H 2 SO 4 cartridge (Hach, Co.) in situ to measure total alkalinity (Hasler et al, 2016;White et al, 2016;Warner et al, 2013). Porewater was filtered with 0.45 µm syringe filters in situ and taken into 5, 15, 15, and 50 ml Nalgene centrifugation tubes for stable isotope, major anion, cation, and nutrient analysis; 250 ml porewater was taken for 222 Rn measurement with RAD7 H 2 O (Durridge, Co.).…”
Section: Sampling and Field Analysismentioning
confidence: 99%